The evolution of S0s with UV bright rings A SWIFT-UVOT study. Issue Volume 11:Issue S321(2015) (21st March 2017) - Rampazzo, R.; Mazzei, P.; Marino, A.; Trinchieri, G.; Uslenghi, M.; Wolter, A.
Abstract: We report about an ongoing study of the evolution of 24 S0s with UV-bright ring/arm-like structures observed with SWIFT-UVOT and interpreted via SPH simulations with chemo-photometric implementation.